Principle components analysis to characterize stress, performance, and injury in female collegiate soccer players - Cook, L. S.; Leigh, S.; Konz, S. (ISBS Proceedings Archive (Michigan), 2021)
Stress created by training is needed to elicit physiological adaptations to increase performance, however, a stress threshold exists. We assessed 19 female collegiate soccer players during an eleven week preparatory phase and measured stress, performance, and injury variables. We used a principal component analysis to determine relationships among stress, performance, and injury. We found a weak, negative relationship between practice stress and anaerobic stress (r = -0.107, p = 0.05), a positive relationship between anaerobic stress and movement risk of injury (r = 0.459, p <.001), and a positive relationship between performance and general risk of injury (r = 0.309, p = 0.003). Sprint distance loaded on four components, and may be an important variable to monitor because it is related to stress, performance, and injury.